The Implementation of Storytelling Technique Used by the English Teacher in Teaching Speaking - Maura Safira; Masrizal Mahmud; Chairina Nasir (Universitas Syiah Kuala, 2020)
This study aims at analyzing the way the teacher develops students speaking performance by using storytelling technique and observing the steps used by the teacher in teaching English. The researcher applied qualitative study by observing classroom teaching practice and interviewing an English teacher at SMKN 1 Banda Aceh. The results of the observations and interview are consistent with the storytelling procedure proposed by Jianing (2007), which are formulated and ordered as deciding the material, dividing students into some groups, assessing the students’ performance and providing them with some feedback at the end of the meeting. The teacher perceived that using storytelling technique in teaching speaking make students to gain more interest in the English classroom because she used storytelling techniques in teaching legend topic. Furthermore, through interview it was revealed that storytelling was believed to have increased student’s vocabulary, confidence and a sense of pleasure in learning English.